Nutritional Assessments Screening Tools on Diabetic Foot Ulcer Healing: A Systematic Review - Ismaila Sonko (South East Asia Nursing Research)
Diabetic foot ulcers (DFUs) are a common and severe complication of diabetes, often leading to prolonged hospital stays, increased healthcare costs, and a higher risk of lower extremity amputations. The role of nutrition in wound healing, particularly in diabetic patients, has been increasingly recognized. This systematic review aims to evaluate the effectiveness of nutritional assessment screening tools in predicting and enhancing the healing outcomes of diabetic foot ulcers. A comprehensive search of relevant databases resulted in the inclusion of 15 studies that met the criteria. The findings suggest that specific nutritional screening tools, such as the Malnutrition Universal Screening Tool (MUST) and the Mini Nutritional Assessment (MNA), are effective in identifying nutritional deficits that could hinder the healing process of DFUs. However, the need for further research to standardize these tools in clinical practice remains imperative.